Investigating the association of bioelectrical impedance analysis–derived phase angle and depressive symptoms in patients receiving maintenance hemodialysis: a cross-sectional study - Huang, Lin; Zhang, Yan; Wang, Jinbao; Zhou, Jiajun (Frontiers in Nutrition, 2025)
BackgroundDepressive symptoms are prevalent among patients undergoing maintenance hemodialysis (MHD), yet its association with phase angle (PhA, a biomarker of nutritional status and cellular integrity) remains unexplored at present. This study aims to investigate the relationship between PhA value and depression in MHD patients.MethodsThis cross-sectional study was performed with 369 MHD patients in China. PhA was measured using bioelectrical impedance analysis, and depressive symptoms (with score ≥ 10) were assessed using the Patient Health Questionnaire. The associations of PhA and depression were assessed using Spearman rank correlation analysis and unadjusted/adjusted binary logistic regression models, controlling for various clinical, biochemical, and demographic factors.ResultsAmong the 369 patients, 17.10% patients (n = 63) had depression with 47.60% of male and median age of 58.50 years. There was a significant decrease in the prevalence of depressive symptoms in patients with the increasing quartiles of PhA levels. Compared patients in Q3 and Q4, MHD patients in the lower quartile groups of PhA (Q1 and Q2) exhibited significantly (p < 0.001) higher cognitive-affective scores and somatic scores. The Spearman correlation and logistic regression analyses revealed the potential associations between depression and several factors, including comorbidities, albumin, PhA, skeletal muscle index, fat free mass, total body water, and extracellular water/total body water (p < 0.05). The unadjusted analysis suggested a significant association between lower PhA values (Q1 and Q2) and higher risk of depressive symptoms. After adjusting for age, sex, and duration of hemodialysis (Model 2), this relationship remained significant for Q1 (OR = 6.051, p < 0.001) and Q2 (OR = 3.309, p = 0.020). In the fully adjusted model (Model 4), the association between low PhA and depressive symptoms was even more pronounced, with the odds of depression in Q1 reaching an OR of 51.760 (p = 0.003).ConclusionLower PhA values were independently and significantly associated with depressive symptoms in MHD patients, suggesting that PhA might serve as an important biomarker for identifying individuals at higher risk for depression. Interventions aimed at improving nutritional status and muscle mass in these patients can potentially reduce the risk of mental deterioration.